Promoting tourism potential in Candirejo Tourism Village, Borobudur, Magelang through a storynomics approach - Ayu, Jati Paras; Octavanny, Vitha; Wibowo DC, Yesi Pandu Pratama; Prabowo, Riky Ramadani (Bahasa Indonesia, 2025)
This study aims to identify the tourism potential of Candirejo Tourism Village through a storynomics tourism approach, which leverages storytelling to create enganging narratives that inspire creative interpretations and imaginations among visitors. The research employs qualitative descriptive research method, gathering primary data through interviews with the head of Candirejo Tourism Village and the local community (Pokdarwis), and secondary data through literature reviews. The result of this research is that the potential possessed by the Candirejo Tourism Village is packaged through a brief description of the narrative of the values ​​contained in the Candirejo tourist village in this research which will be displayed on the official website, namely candirejo.com, in the form of a Flipping Book.The study suggested that Candirejo Tourism Village promotes tourism by utilizing storynomic narratives, presented through creative and interactive media such as digital flipbooks, to attract tourist and enrich their experience of Candirejo’s tourism before visiting Candirejo tourist village.